Overcommitted to tourism and under committed to sustainability: the urgency of teaching "strong sustainability" in tourism courses. Issue 7 (3rd July 2019) - Cotterell, Debbie; Hales, Robert; Arcodia, Charles; Ferreira, Jo-Anne
Abstract: With the tourism sector being urged to contribute to the UN's 2030 Sustainable Development Goals (SDGs), tourism educators need to develop industry leaders with "strong sustainability" mindsets. "Sustainable development" has long been contested as a weaker form of sustainability due to its "pro-growth" emphasis. Research suggests that tourism students are graduating with narrow understandings of sustainability, partly due to course designs based on weaker conceptualisations of sustainability and a lack of holistic, critical and systemic thinking. The purpose of this paper is to analyse – using content analysis – the strength of sustainability conceptualisations underpinning international undergraduate sustainable tourism courses, which has not previously been carried out. Results indicate that sustainable tourism courses do not include "very strong" conceptualisations of sustainability, and that sustainability pedagogy and approaches such as systems and holistic thinking are not widely used. This paper argues that stronger conceptualisations and sustainability skills are essential. A framework is also suggested to assist tourism educators to use critical reflective thinking in conjunction with the SDGs to assist the development of more complex ways of thinking and acting towards achieving global sustainable tourism outcomes. The discussion concludes with suggestions for further research to ensure stronger sustainable tourism curricula.